Życie codzienne mieszkańców Pleszewa w 2. połowie XVIII wieku - Makowski, Artur (My University, 2019)
Temat rozprawy doktorskiej mieści się w obszarze badań nad problematyką miast i miasteczek Rzeczypospolitej w czasach nowożytnych. Badania przedstawione w niniejszej dysertacji zostały poświęcone różnym aspektom życia codziennego mieszczan pleszewskich w 2. poł. XVIII w. Obszar chronologiczny obejmuje lata 1750-1793. Zakres przestrzenny podjętego tematu odnosi się do obszaru miasta lokacyjnego wraz z przedmieściami. Praca składa się ze wstępu, pięciu rozdziałów, zakończenia oraz dziewięciu aneksów. Rozdział pierwszy poświęcony jest ogólnej charakterystyce obrazu miasta. Rozdział drugi, najobszerniejszy, przedstawia ustrój miasteczka. Rozdział trzeci traktuje o kwestiach dotyczących społeczeństwa. Zawiera szczegółowe informacje o demografii miasteczka, m.in. dane o liczbie ludności, analizę ślubów, chrztów oraz zgonów. Rozdział czwarty charakteryzuje gospodarkę miejską. W rozdziale piątym zaprezentowano sprawy kulturalne Pleszewa.

The subject of the doctoral dissertation is in the field of research on the problems of towns and cities of the Polish-Lithuanian Commonwealth in modern times. The research presented in this dissertation has been devoted to various aspects of everyday life of the Pleszew burghers in the second half of the 18th century. The chronological area covers the years 1750-1793. The spatial extent of the subject is related to the city of the city with the suburbs. The work consists of an introduction, five chapters, an ending and nine annexes. The first chapter is devoted to the general characteristics of the city image. The second, most comprehensive chapter presents the system of the town. The third chapter deals with issues concerning society. It contains detailed information about the town's demographics, including data on the population, analysis of marriages, baptisms and deaths. The fourth chapter characterizes the urban economy. In the fifth chapter, Pleszew's cultural matters were presented.
The everyday life of the Pleszew burghers in the second half of the 18th century
Wydział Historyczny
Keywords: nowożytność; modern age; Pleszew; mieszczaństwo; miasteczko; middle class; small town